Development of a variable frequency power electronics inverter to control the speed of a three-phase induction motor - Neves, Pedro (2006)
This work presents the development and implementation of a variable frequency Power Electronics inverter to drive a three-phase induction motor. The inverter allows a user to control the speed and torque developed by the motor, as well as its rotating direction. The inverter’s digital controller was implemented with a microcontroller. The inverter is fed from a rectifier with capacitor filter, which is connected to single-phase, 50 Hz power mains.